The Marital Adjustment Dynamics of Ahmadi and Non-Ahmadi Descent of the Ahmadiyya Jamaat in Indonesia: [Dinamika Penyesuaian Perkawinan Pasangan Keturunan dan Bukan Keturunan Anggota Jemaat Ahmadiyah di Indonesia] - Yunifa, Putri; Afiatin, Tina (Faculty of Psychology, Universitas Surabaya, 2023)
Marital adjustment between couples with different and stigmatized religious backgrounds has rarely been studied. This study aims to explain the dynamics of marital adjustment for Ahmadiyya members who are of Ahmadi descent and married to individuals of non-Ahmadi descent using a multiple case study approach. This study conducted in-depth interviews with four couples from Indonesian Ahmadiyya Muslim Congregation, consisting of two husband and wife couples with husbands of Ahmadi descent, and two husband and wife couples of Ahmadi descent. Data were analyzed with a cross-case synthesis. Personality factors (socialization and achievement) that are followed by adaptation have shaped the marital adjustments of the four husbands and wives of Ahmadi descent in this study. Personality strengthens relational commitments which play an important role in marital adjustment. In active Ahmadi couples, personality factors strengthen the religious commitment of the spouses, but they also compromise their partner's shortcomings in religious matters. Personality factors also encourage them to continue to show tolerance and generosity towards extended families who have shown a stigmatizing attitude towards them as Ahmadis. This study implies the importance of considering personality factors that predict partner adjustment and not only religiosity or religious background in marriages among religious groups. Penyesuaian perkawinan antara pasangan dengan latar belakang keagamaan berbeda dan terstigmatisasi jarang dipelajari. Studi ini bertujuan menjelaskan dinamika penyesuaian perkawinan anggota Jemaat Ahmadiyah keturunan Ahmadi yang menikah dengan individu bukan keturunan Ahmadi dengan pendekatan studi kasus majemuk. Studi ini melakukan wawancara mendalam kepada empat pasang suami-istri anggota Jemaat Ahmadiyah Indonesia (JAI) yang terdiri dari dua pasang suami-istri dengan suami keturunan Ahmadi, dan dua pasang suami-istri dengan istri keturunan Ahmadi. Data dianalisis dengan sintesis lintas kasus. Faktor kepribadian (socialization dan achievement) yang diikuti dengan adaptasi membentuk penyesuaian perkawinan pada keempat suami-istri lintas keturunan Ahmadi tersebut. Kepribadian memperkuat komitmen relasional yang berperan penting dalam penyesuaian perkawinan. Pada pasangan Ahmadi yang aktif, faktor kepribadian memperkuat komitmen religius suami-istri, namun mereka juga berkompromi dengan kekurangan pasangan mereka dalam hal keagamaan. Faktor kepribadian juga mendorong mereka tetap menunjukkan toleransi dan kemurahan hati terhadap keluarga besar yang pernah menunjukkan sikap stigmatik terhadap mereka sebagai Ahmadi. Studi ini mengimplikasikan pentingnya mempertimbangkan faktor kepribadian yang memprediksi penyesuaian pasangan dan bukan hanya religiusitas atau latar belakang keagamaan dalam perkawinan di kalangan kelompok keagamaan.